PERCEPTION OF ACCEPTANCE OF TAX EVASION BY MANAGERS OF MICRO AND SMALL COMPANIES IN VITÓRIA/ES - dos Santos, Geise Senhora; Dumer, Miguel Carlos Ramos; Nunes, Julyana Goldner; Cavalcante, Levy Daniel; dos Santos, Alana Daniely Santana; Azevedo, Filipe Bressanelli; Lopes, Sergio Rufus Lima; Lopes, Sinara Silva Pinheiro (Seven Editora, 2025)
The purpose of this study was to address the main reasons that lead micro and small companies to opt for tax evasion. Aiming at their own well-being in the face of fiscal and tax obligations, these companies use illicit means and loopholes in the legislation to obtain favorable results on their taxes. Due to the constant search to achieve the reduction of taxes, the Municipal, State and Federal agencies have adopted methods that provide inspection in the fulfillment of obligations. These methods have become possible due to the tools that store data in the database of the responsible agencies, data that refers to the operations carried out by the company, especially information about the value of its revenue. Through the tool used by these inspection agencies, it became possible to control and analyze the data transmitted to these agencies. Thus, the present work aims to identify and evidence, the results of a research published on an online platform, on the main factors that motivate the managers of companies established in the state of Espírito Santo, in the municipality of Vitória, to use fraudulent attitudes to not comply with their fiscal and tax obligations. It identified the profile of companies, managers, and that many managers accept to use illegal methods to obtain even more reduction in their taxes, even knowing that this act may cause future consequences.DOI: https://doi.org/10.56238/sevened2024.037-119